2015
DOI: 10.1021/acs.jpcc.5b03396
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Li Microstructure Formation on Li Anodes for Lithium Batteries by in Situ 6Li/7Li NMR and SEM

Abstract: The growth of lithium microstructures during battery cycling has, to date, prohibited the use of Li metal anodes and raises serious safety concerns even in conventional lithium-ion rechargeable batteries, particularly if they are charged at high rates. The electrochemical conditions under which these Li microstructures grow have, therefore, been investigated by in situ nuclear magnetic resonance (NMR), scanning electron microscopy (SEM) and susceptibility calculations. Lithium metal symmetric bag cells contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
163
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(185 citation statements)
references
References 48 publications
12
163
1
Order By: Relevance
“…3 displays orthogonal cross-sections of the B 0 field map obtained from the susceptibility calculations and a histogram showing the variation in the B 0 field across the full voxel. A significant perturbation of 10-15 ppm is observed in the B 0 field close to the dendrite, matching well with 7 Li MRI (7, 10) and NMR (6,8,21) results, where the signals from the dendrites are observed to shift by up to 15 ppm relative to the bulk metal resonance. The effects are long-ranged, impacting the local field for all of the positions inside the voxel, albeit by small amounts.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…3 displays orthogonal cross-sections of the B 0 field map obtained from the susceptibility calculations and a histogram showing the variation in the B 0 field across the full voxel. A significant perturbation of 10-15 ppm is observed in the B 0 field close to the dendrite, matching well with 7 Li MRI (7, 10) and NMR (6,8,21) results, where the signals from the dendrites are observed to shift by up to 15 ppm relative to the bulk metal resonance. The effects are long-ranged, impacting the local field for all of the positions inside the voxel, albeit by small amounts.…”
Section: Resultssupporting
confidence: 85%
“…NMR measurements are sensitive to dendrite growth and are also able to resolve different lithium microstructure morphologies through chemical shift measurements (6)(7)(8)(9). MRI approaches provide additional spatial information, allowing specific structural changes to be localized, thereby enhancing the utility of the methods and simplifying interpretation (7,10,11).…”
mentioning
confidence: 99%
“…[12][13][14]17,[22][23][24] Interestingly, the 3d CSI sheds new light on previous bulk metal NMR studies. For instance, in an earlier study, 12 a similar shift difference between NMR peaks was observed at and ⊄ orientations (relative to B 0 ) of the major faces of a thinner metal strip, by carrying out two separate experiments.…”
Section: Csimentioning
confidence: 88%
“…In order to deeply investigate the processes occurring in the novel electrochemical energy storage systems based on lithium metal anode, the combination of electrochemical techniques with bulk and advanced spectroscopic ones is mandatory. In this context, nuclear magnetic resonance (NMR) spectroscopy plays a key role to understand the processes taking place in a battery . NMR exploits the magnetic properties of atomic nuclei to find out information on the chemical environment in molecules and solids, as well as on its changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, nuclear magnetic resonance (NMR) spectroscopy plays a key role to understand the processes taking place in a battery. [13][14][15][16] NMR exploits the magnetic properties of atomic nuclei to find out information on the chemical environment in molecules and solids, as well as on its changes over time. This last task is fulfilled by measuring the relaxation times of chemical species, namely T 1 and T 2 .…”
Section: Introductionmentioning
confidence: 99%